Dynamics and Development of Confucianism in Indonesia - Nadya Putri; Naufal Arib Maulana Hasibuan; Wahida Sitanggang; Khairil Andrean (Sufiya Research Institute, 2023)
There are many religions that grow and develop in this world. Hinduism, Buddhism, Judaism, Christianity and Islam are religions with a large number of followers. There are also religions whose number of followers is not the same as the religions mentioned but these religions are still known among the world's religious communities, such as Zoroastrian, Shinto, Jain, Confucian, Sikh, and Baha'i religions. The presence of such religions in one community is something that can produce diversity as well as plurality of religions. In this discussion, we only discuss Confucianism. Therefore, the question arises about the history and development of Confucianism in the world. This journal is summarized using the literature study method. The purpose of writing this journal is to find out the history and development of Confucianism, especially in Indonesia. The results obtained from this paper are Confucianism, which is also known as Confucianism. Confucianism is the oldest religion in China. Confucianism is a religion which, with its teachings, provides its followers with teachings towards the ideal human traits as individuals themselves or in their lives in society. Confucianism has given a deep impression on life and culture in China, because this religion has various teachings on love, hospitality, courtesy, as well as philosophy, the teachings of which are embodied in that religion.